CI431, an Aqueous Compound from Ciona intestinalis L., Induces Apoptosis through a Mitochondria-Mediated Pathway in Human Hepatocellular Carcinoma Cells. (21st July 2011) - Cheng, Linyou; Liu, Ming; Wang, Cuicui; Liu, Haizhou; Zhang, Yuyan; Lin, Xiukun
Abstract : In the present studies, a novel compound with potent anti-tumor activity from Ciona intestinalis L. was purified by acetone fractionation, ultrafiltration, gel chromatography and High Performance Liquid Chromatography. The molecular weight of the highly purified compound, designated CI431, was 431Da as determined by HPLC-MS analysis. CI431 exhibited significant cytotoxicity to several cancer cell types. However, only a slight inhibitory effect was found when treating the benign human liver cell line BEL-7702 with the compound. To explore its mechanism against hepatocellular carcinoma, BEL-7402 cells were treated with CI431 in vitro. We found that CI431 induced apoptotic death in BEL-7402 cells in a dose- and time-dependent manner. Cell cycle analysis demonstrated that CI431 caused cell cycle arrest at the G2/M phase, and a sub-G1 peak appeared after 24 h. The mitochondrial-mediated pathway was implicated in this CI431-induced apoptosis as evidenced by the disruption of mitochondrial membrane potential. The results suggest that the CI431 induces apoptosis in BEL-7402 human hepatoma cells by intrinsic mitochondrial pathway.